Investigation of signal characteristics from the non-destructive testing of weld specimens - Ong, Chin Yong (2016)
Ultrasonic testing has found a very important standing in the aerospace, oil and gas and many other industry sectors including up and coming additive manufacturing. Ultrasonic testing is a non-destructive technology that performs quality checks on metallic specimens to detect defects efficiently and effectively. These industries need ultrasonic testing as ultrasonic testing makes the work easier for the operator to diagnose defects (cracks) on areas like huge pipes, structural joints and perform preventive measures without having to shut down the entire operation that often saving huge costs before catastrophic effect takes place (oil spills that destroy the wildlife at sea). Ultrasonic testing is always revolving in the areas of A-scan, B-scan, C-scan, S-scan to bring non-destructive technology to a whole new level. This will further enhance the ability of quality assurance and management of ultrasonic testing giving a more accurate and reliable inspection data. The inspection data is also presented in better form for the operators to differentiate the different signal amplitudes and allow them to decide to further investigate the defect or discontinuity. There are various standards and codes in the industry that set the bar for the application of NDT in the area of the ultrasonic testing. These codes and standards are set based on the consensus of all the subject matter experts who contributed inputs with their knowledge and experience from qualifying personnel to the way the information should be presented. This helps people to interpret the inspection information easily and reach a quicker understanding of the content regardless of where they can be as standards and codes have broken down barrier for misunderstanding.